2008
DOI: 10.1371/journal.pbio.0060045
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Evidence for a Pervasive Alteration in Tropical Tree Communities

Abstract: In Amazonian tropical forests, recent studies have reported increases in aboveground biomass and in primary productivity, as well as shifts in plant species composition favouring fast-growing species over slow-growing ones. This pervasive alteration of mature tropical forests was attributed to global environmental change, such as an increase in atmospheric CO2 concentration, nutrient deposition, temperature, drought frequency, and/or irradiance. We used standardized, repeated measurements of over 2 million tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
252
4
7

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 202 publications
(278 citation statements)
references
References 53 publications
(72 reference statements)
15
252
4
7
Order By: Relevance
“…Violation of this could lead to artificially low confidence intervals. On BCI, as Chave et al (2008) previously reported for this and other large plots, the confidence intervals are insensitive to the subplot scale for subplot sizes between 0.025 and 1 ha (Figure 14.2B), consistent with the lack of spatial structure at these scales (Figure 14.2A). The sampling uncertainty for the full 50-ha plot that is estimated by bootstrapping over subplots is exactly consistent with the spatial scaling of sampling uncertainty for smaller areas (Figure 14.1A).…”
Section: E T E C T I N G a N D P R O J E C T I N G C H A N G E S Isupporting
confidence: 87%
See 4 more Smart Citations
“…Violation of this could lead to artificially low confidence intervals. On BCI, as Chave et al (2008) previously reported for this and other large plots, the confidence intervals are insensitive to the subplot scale for subplot sizes between 0.025 and 1 ha (Figure 14.2B), consistent with the lack of spatial structure at these scales (Figure 14.2A). The sampling uncertainty for the full 50-ha plot that is estimated by bootstrapping over subplots is exactly consistent with the spatial scaling of sampling uncertainty for smaller areas (Figure 14.1A).…”
Section: E T E C T I N G a N D P R O J E C T I N G C H A N G E S Isupporting
confidence: 87%
“…Since the biomass change on the plot is known more exactly, this bootstrapping procedure is technically estimating sampling uncertainty associated with the stochastic process operating within this plot (and that could potentially have produced other outcomes) (e.g. Chave et al 2008). When dividing a plot into subplots for the purposes of within-plot bootstrapping, it is essential that the subplot scale be greater than the integral length scale, the scale at which the spatial semivariogram plateaus, i.e.…”
Section: E T E C T I N G a N D P R O J E C T I N G C H A N G E S Imentioning
confidence: 99%
See 3 more Smart Citations